2019
DOI: 10.1136/bmjopen-2019-030342
|View full text |Cite
|
Sign up to set email alerts
|

Trends and predictors of biomedical research quality, 1990–2015: a meta-research study

Abstract: ObjectiveTo measure the frequency of adequate methods, inadequate methods and poor reporting in published randomised controlled trials (RCTs) and test potential factors associated with adequacy of methods and reporting.DesignRetrospective analysis of RCTs included in Cochrane reviews. Time series describes the proportion of RCTs using adequate methods, inadequate methods and poor reporting. A multinomial logit model tests potential factors associated with methods and reporting, including funding source, first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Comparison with other studies A previous study evaluating overall quality of methods in biomedical RCTs, including randomisation, blinding and selective reporting, concluded that 59.3% of RCTs used inadequate methods (meaning scoring high risk of bias on one or more of the six Cochrane risk of bias items) and 35% of RCTs were poorly reported (meaning providing not enough information in the methods to decide on adequate or inadequate methods). 28 Comparable findings have been found in physiotherapy RCTs in the PEDro database 23 and evaluation of manual therapy trials. 29 30 While reporting of effect estimates in our selection of high-quality physiotherapy literature differs between 2000 and 2018, still most papers did not adhere to the reporting recommendations provided by the ASA and CONSORT-statements with regards to statistical significance testing and reliance on p values to interpret results.…”
Section: Open Accessmentioning
confidence: 68%
“…Comparison with other studies A previous study evaluating overall quality of methods in biomedical RCTs, including randomisation, blinding and selective reporting, concluded that 59.3% of RCTs used inadequate methods (meaning scoring high risk of bias on one or more of the six Cochrane risk of bias items) and 35% of RCTs were poorly reported (meaning providing not enough information in the methods to decide on adequate or inadequate methods). 28 Comparable findings have been found in physiotherapy RCTs in the PEDro database 23 and evaluation of manual therapy trials. 29 30 While reporting of effect estimates in our selection of high-quality physiotherapy literature differs between 2000 and 2018, still most papers did not adhere to the reporting recommendations provided by the ASA and CONSORT-statements with regards to statistical significance testing and reliance on p values to interpret results.…”
Section: Open Accessmentioning
confidence: 68%
“…Specifically, an average of three to four-person teams produced each multi-authored paper. Existing SciTS literature has stated that co-authors are more heavily cited than single-authors, an increase in authors leads to increased research impact, and increasing team size predicts research quality increases (4,5,37).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, an average of three to four-person teams produced each multi-authored paper. Existing SciTS literature has stated that co-authors are more heavily cited than single authors, an increase in authors leads to increased research impact, and increasing team size predicts research quality increases [4,5,37]. The average CNTN research team size is equal to the observed average team size across the landscape of science, engineering, and social sciences [5].…”
Section: Discussionmentioning
confidence: 99%
“…Despite exponential growth in the number of clinical trials conducted yearly over the past two decades [ 5 ], multiple authors contend that the methodological quality of clinical trials has remained stagnant or even declined [ 6 , 7 ], such that true practice-guiding evidence on a broad range of medial topics paradoxically lags behind [ 8 , 9 , 10 ]. Blinding is one aspect of clinical trial design that remains particularly underutilized—although this methodological feature is not universally attainable, blinding is still implemented in only a fraction of clinical trials in which it is, in fact, deemed feasible [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%